MODEL PREDIKSI KELIMPAHAN NITZSCHIA SP. DI PERAIRAN TELUK HURUN, LAMPUNG - Septiana Widi Lestari; Tugiono; Endro P. Wahono; Rinawati (Techno-Fish, 2022)
The aim of this research was to study the factors that influence the potential diatom abundance of Harmful Algal Blooms (HABs) Nitzschia sp. and make a prediction model for the abundance of Nitzschia sp. in the waters of Hurun Bay, Lampung. Factors affecting the abundance of Nitzschia sp. were salinity, pH and ammonia. The abundance prediction model of Nitzschia sp. carried out using multiple regression with the method of selecting Backward variables and 95% confidence level with the results of R2 for Nitzschia sp. by 23.2% . Based on the results of the validation with the sample t-2 test, the prediction model of Nitzschia sp. cannot be used to predict the abundance of Nitzschia sp. in the future. There is still a need for in-depth research on other factors that influence the blooming of Nitzschia sp. so that a predictive model of the abundance of Nitzschia sp. can be generated better. It is still necessary to model the prediction of the abundance of Nitzschia sp. with other methods so as to produce predictive values ​​that are closer to reality. Keywords: Regression model, prediction, HABs, Nitzschia, Hurun Bay.